2021
DOI: 10.1021/acssuschemeng.1c03685
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenolysis of Lignin Model Compounds to Aromatics over a Cobalt Nanoparticle Catalyst

Abstract: Catalytic conversion of renewable lignin to aromatics can effectively alleviate the fossil resource crisis. Herein, we prepared porous nitrogen-doped carbon-supported cobalt nanoparticle catalyst (CoNC) using a SiO2 template and tested its catalytic performance for cleavage of the β-O-4 ether bond in lignin model compounds. It was found that the catalyst pyrolyzed in a nitrogen atmosphere at 900 °C (CoNC-900) could catalyze 2-phenoxyacetophenone to ethylbenzene and phenol effectively, affording both in 99.0% y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…In addition, when the reaction time is longer than 4 h, the conversion and the yields of phenol and ethylbenzene remained nearly constant as shown in Fig. 4(a 45 . Thus, in this work, transfer hydrogenolysis of a lignin b-O-4 ketone model compound, 2-phenoxyacetophenone, was further explored over Ni@NC-800, Ni@NC-800-H and Ni/NC-800.…”
Section: Catalytic Activity Evaluationmentioning
confidence: 74%
See 2 more Smart Citations
“…In addition, when the reaction time is longer than 4 h, the conversion and the yields of phenol and ethylbenzene remained nearly constant as shown in Fig. 4(a 45 . Thus, in this work, transfer hydrogenolysis of a lignin b-O-4 ketone model compound, 2-phenoxyacetophenone, was further explored over Ni@NC-800, Ni@NC-800-H and Ni/NC-800.…”
Section: Catalytic Activity Evaluationmentioning
confidence: 74%
“…Recently, a two-step strategy has been proposed in the transformation of lignin β-O-4 model compounds: the oxidation of C α –OH of β-O-4 alcohol to β-O-4 ketone, which can lower the C β –O bond dissociative energy (BDE) by 40–50 kJ mol −1 , followed by the hydrogenolysis of the C β –O bond 45 . Thus, in this work, transfer hydrogenolysis of a lignin β-O-4 ketone model compound, 2-phenoxyacetophenone, was further explored over Ni@NC-800, Ni@NC-800-H and Ni/NC-800.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the addition of Ru could improve the hydrogenolysis reactivity. Wu et al [16] reported that 2-phenoxyacetophenone could be converted to ethylbenzene and phenol with 99.0 % yields over CoNC catalyst at 220 °C. Mauriello et al [13b] reported that Pd/Co catalyst could convert benzyl phenyl ether to toluene and cyclohexanol with 50 % yields at 240 °C.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the addition of Ru could improve the hydrogenolysis reactivity. Wu et al [16] . reported that 2‐phenoxyacetophenone could be converted to ethylbenzene and phenol with 99.0 % yields over CoNC catalyst at 220 °C.…”
Section: Introductionmentioning
confidence: 99%